2021
DOI: 10.3390/cancers13143593
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated T2-Weighted TSE Imaging of the Prostate Using Deep Learning Image Reconstruction: A Prospective Comparison with Standard T2-Weighted TSE Imaging

Abstract: Multiparametric MRI (mpMRI) of the prostate has become the standard of care in prostate cancer evaluation. Recently, deep learning image reconstruction (DLR) methods have been introduced with promising results regarding scan acceleration. Therefore, the aim of this study was to investigate the impact of deep learning image reconstruction (DLR) in a shortened acquisition process of T2-weighted TSE imaging, regarding the image quality and diagnostic confidence, as well as PI-RADS and T2 scoring, as compared to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
7
40
1
Order By: Relevance
“…It was shown that DL image reconstructions are possible with high image quality in musculoskeletal imaging, abdominal imaging, and in prostate MRI including drastic reduction of acquisition time. 29,30 However, in GRE imaging most approaches were related to improvement of image quality and resolution (superresolution) and not primarily to acquisition time due to the fast imaging process. 19 The successful application of superresolution was previously demonstrated in head and neck and knee imaging as well as in precontrast and postcontrast abdominal MRI.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that DL image reconstructions are possible with high image quality in musculoskeletal imaging, abdominal imaging, and in prostate MRI including drastic reduction of acquisition time. 29,30 However, in GRE imaging most approaches were related to improvement of image quality and resolution (superresolution) and not primarily to acquisition time due to the fast imaging process. 19 The successful application of superresolution was previously demonstrated in head and neck and knee imaging as well as in precontrast and postcontrast abdominal MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, a severe limitation of these sequences is based on its long acquisition times and reduced scanner availability. In recent studies, it was shown that DL image reconstruction is able to achieve an acquisition time reduction of up to 65% in prostate TSE imaging, without any loss of image quality ( Figure 2 ) [ 11 , 38 ].…”
Section: Deep Learning Applications In Radiologymentioning
confidence: 99%
“…In radiology, trained algorithms based on larger datasets have primarily been introduced in, e.g., classification, segmentation, pattern recognition, and artificial intelligence-based diagnosis [ 13 , 14 ]. In the meantime, the inclusion of these components into the reconstruction process has enabled great improvements in image quality, sharpness, and signal-to-noise ratio (SNR) in MRI and has consequently also accelerated acquisitions [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%